Females prefer good genes: MHC-associated mate choice in wild and captive tuco-tucos - Cutrera, Ana Paula (2012)
The major histocompatibility complex (MHC) genes are one of the most suitable candidates for elucidating the genetic bases of mate choice in vertebrates, given the potential benefits in terms of immunocompetence that can be passed to the offspring through MHC-associated mate choice. Female mate choice may favour males that possess particular MHC alleles or those with diverse MHC genotypes (good genes hypothesis), or males that possess MHC genotypes that differ from that of the female (compatibility hypothesis). Our goal was to evaluate mate choice in relation to MHC genotype in the subterranean rodent Ctenomys talarum. Using both laboratory and field analyses, we investigated whether the (1) number of shared MHC alleles between males and females, (2) number of amino acid differences between female and male MHC alleles, (3) MHC heterozygosity of males, (4) number of amino acid differences between male MHC alleles, and (5) frequency of MHC alleles of males differ between preferred and nonpreferred males in the laboratory and between potential sires and random males from the population in the field. In the laboratory, our results indicate that MHC alleles of preferred males differ in fewer amino acids compared to MHC alleles of nonpreferred males. Concomitantly, in the field,MHC alleles of possible sires differed in fewer amino acids than those of random males in the population. Plus, possible sires were more heterozygous and carried distinct MHC alleles compared with random males, thus providing more support to the "good genes" hypothesis. We discuss the possible reasons why MHC-based mate choice was more evident in the field and the implications of such a female mating strategy in the subterranean environment.